Comparison between low and high pressure negative pressure wound therapy (NPWT) in diabetic foot wound in term of wound size reduction and wound bed preparation for secondary procedure - Zarullail, Nor Hafizah (2020)
Introduction: Healing of diabetic foot ulcer is often a challenging problem due to lack of resistance against infection and presence of peripheral arterial disease in diabetic patients. The use of negative pressure wound therapy (NPWT) to facilitate the healing of diabetic foot ulcer had been studied by many people. To date, the optimal pressure for NPWT was -125mmHg. The aim of this study is to compare the effectiveness of low pressure (-50 mmHg) and high pressure (-100 mmHg) NPWT in term of wound size reduction and optimal wound bed preparation for secondary procedure. Methodology: This was a prospective interventional, randomized controlled trial study done on patients with diabetic foot ulcer admitted to orthopaedic ward, Hospital Universiti Sains Malaysia. A total of 58 patients which were randomly assigned into 2 groups either low pressure (-50 mmHg) or high pressure (-100 mmHg) NPWT and the outcome measured were wound size reduction and wound bed score. Patients demographic data were collected and statistical analysis was done using repeated measure analysis of variance (ANOVA) to determine the relationship between the treatment and outcomes measured. Result: Both treatment groups show significance changes in term of wound size reduction and wound bed score. However there is no significance difference when comparing in between both treatment group with measured outcomes. Discussion/Conclusion: Negative pressure wound therapy facilitate the healing of diabetic foot ulcer by reducing the wound size and expediates wound bed preparation for secondary procedure even though there were no significance difference in between the level of negative pressure used. The level of negative pressure used should be tailored to individual patient and the aim of treatment.